2003
DOI: 10.1016/s0378-1127(02)00027-0
|View full text |Cite
|
Sign up to set email alerts
|

Foliar nutrient status and nutritional relationships of young Pinus radiata D. Don plantations in northwest Spain

Abstract: Fifty-four plots of young Pinus radiata D. Don plantations on abandoned agricultural land in Galicia (northwest Spain) were selected for nutritional diagnosis. Nutritional status was assessed by foliar analysis using the critical levels method. The relationships between foliar nutrient concentrations and the plantation's growth and survival and the topsoil physical and chemical properties were also analyzed. The most common deficiencies among plots were P and Mg. Foliar N concentrations were relatively high an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
2
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 20 publications
7
37
2
2
Order By: Relevance
“…The least fertile soils with low levels of available P generally had a shallow soil depth. Similar deficiencies, particularly in P and extractable bases have been observed in acid forest soils under radiata pine plantations in Spain (Romanyà and Vallejo, 1996;Zas, 2003;Zas and Serrada, 2003). Romanyà and Vallejo (2004) showed that Atlantic radiata pine plantations grow in soils rich in organic matter and N and in shallow soils with low pH, low available P and general low fertility.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…The least fertile soils with low levels of available P generally had a shallow soil depth. Similar deficiencies, particularly in P and extractable bases have been observed in acid forest soils under radiata pine plantations in Spain (Romanyà and Vallejo, 1996;Zas, 2003;Zas and Serrada, 2003). Romanyà and Vallejo (2004) showed that Atlantic radiata pine plantations grow in soils rich in organic matter and N and in shallow soils with low pH, low available P and general low fertility.…”
Section: Resultssupporting
confidence: 58%
“…Asturian forest soils are characterized by moderate or shallow depth, high organic matter content in the upper horizon, and high or moderate acidity (pH around 4), except in eastern Asturias, where most of the rocks are basic (Guitian et al, 1985). The Spanish radiata pine plantations are not fertilized resulting in widespread nutritional deficiencies (Romanyà and Vallejo, 1996;Zas and Serrada, 2003). The soils were classified as Ustorthent, Ustochrept and Dystrochrept (Soil Survey Staff, 1999) developed on whitish quartzite (9 stands), black slate (8), feldspar sandstone (15), and conglomerate (6) (IGME, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations